79 Implementing Cardiovascular Preparticipation Screening Examinations in Rural Idaho. (1st January 2006) - Johnson, S.; Tubbs, K. J.
Abstract : Sudden cardiac death (SCD), while a rare event, is currently the leading cause of death associated with high school athletics in the United States. SCD encompasses a number of conditions, with hypertrophic cardiomyopthy being considered the most common among high school athletes in the US. In 1996, the American Heart Association (AHA) recommended a cardiovascular preparticipation evaluation (PPE) for all high school students participating in athletics and outlined guidelines for such an examination. In rural communities, the responsibility to perform such screenings likely falls on the shoulders of local family physicians. While there are published reports of large-scale screening programs utilizing numerous physicians and resources, to our knowledge there are no descriptions in the literature of PPEs performed by family physicians in rural communities. Due to the large number of family physicians serving rural areas in the US, reports of this nature could prove valuable in shaping a standard PPE suitable to a rural community. We will report the results of a PPE initiated in Malad, Idaho, a community of approximately 3, 000 people. The parents of 66 prospective ninth graders were offered the opportunity to allow their child to participate in a free PPE. Thirty-three of the children were screened. The PPE consisted of a cardiac history and physical in line with the AHA's 1996 recommendations, along with a 12-lead electrocardiogram. Ten children were identified as needing further evaluation (ie, echocardiography) or referral to a cardiologist. The protocol for the examinations will be presented along with the approximate time, cost, and manpower required to implement this program in Malad, Idaho.